Green Synthesis of Zinc Oxide Nanoparticles from Fruits and Leaf Extract of Cordia dichotama - Jayamma, P.; Deepthi, K. Sai; Divya, N.; Abhinaya, B.; Tangirala, A. D. Srikanth; Madhavi, Bijjam (International Journal of Economic Plants, 2026)
The study was conducted from February, 2023 to May, 2025 in the Department of Food Safety and Quality Assurance, College of Food Science and Technology, Acharya N. G. Ranga Agricultural University, Pulivendula, with an aim to prepare a uniform, ultrafine ZnO NPs using a process that saves time and energy. The solution combustion synthesis (SCS) approach was adopted for the preparation of zinc oxide (ZnO) nanoparticles using Cordia dichotoma L. leaf extract as a fuel and reducing agent, aiming to obtain uniform, ultrafine ZnO nanoparticles through a time- and energy-efficient process. Green synthesis using plant materials, vegetables, enzymes, and microorganisms had gained considerable attention due to its eco-friendly, economical, and simple nature. Among biological methods, plant extract-based synthesis had emerged as a promising alternative. In this work, ZnO nanoparticles were synthesized using both leaf and fruit extracts of C. dichotoma through a self-sustaining reaction between zinc acetate and the extracts. The synthesized nanoparticles were characterized using UV-Visible spectroscopy, scanning electron microscopy (SEM), energy-dispersive X-ray (EDX) analysis, and X-ray diffraction (XRD). UV-Vis spectra exhibited absorption peaks between 350–390 nm, confirming nanoparticle formation. XRD revealed a strong peak at 37°, corresponding to the wurtzite structure. SEM analysis showed particle sizes ranging from 3–10 nm, while EDX confirmed high purity. The antioxidant activity of leaf-extract-derived ZnO nanoparticles was higher than that of fruit-extract-derived ones and increased with nanoparticle concentration. Antibacterial activity was more effective against Escherichia coli (Gram-negative) than Staphylococcus aureus (Gram-positive). Overall, C. dichotoma-mediated ZnO nanoparticles exhibited excellent antioxidant and antibacterial potential for biomedical and food safety applications.